SOCIAL AND COMMUNICATIVE ASPECTS OF SELF-PRESENTATION AS A COMPONENT OF A DESIGNER'S PERSONAL BRAND - Удріс-Бородавко, Н. С. (Art and Design, 2024)
The purpose of the article is to study the experience of self-presentation by leading Ukrainian designers and to reveal those aspects that will contribute to the effectiveness of their personal brands in the context of strengthening the importance of the design sector in the socio-cultural development of Ukraine. To achieve the tasks, the methods of systematic analysis and concretization in the study of theoretical researches and content of individual pages of designers in social networks, methods of comparison and synthesis of the different pages content of one designer, and the method of induction to summarize the current situation and conclusions were used. Among the effective content of self-presentation are social responsibility, personal autobiographical stories, and demonstration of teamwork. It is emphasized that social responsibility is a determining factor in brand positioning and communication. In the context of personal brands of designers, this thesis is of particular importance, because they are the carriers of the profession of a potentially influential social sector of culture and economy. The areas of social responsibility should be those in which the designer has the opportunity to make real positive changes. Autobiographical content can reveal stories of certain achievements and successes of the designer, demonstrate his or her hobbies, personal sphere, and family ties. An important aspect of self-presentation is when a designer presents himself or herself as part of a professional team, as he or she usually works with a group of specialists who ensure the completeness of projects. The functional division of responsibilities in project work and the proper management of interactions ensure a successful outcome. Therefore, designers should demonstrate their understanding of the importance of the team through various communication channels. The scientific novelty lies in the content of the model of a designer's personal brand, in particular, its component of self-presentation, and in the analysis of the self-presentation experience in social media of leading Ukrainian designers. The practical significance lies in the possibility for designers to apply the recommendations for creating a self-concept and building a self-presentation strategy for their personal brand on its basis.